(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Construction projects (particularly infrastructure) necessitate large capital investments both during construction and operation, accounting for 3 to 8% of a developing country’s GDP. Construction and supporting economic activity account for roughly half of all investments in the economy. The construction sector in developing nations must be incorporated in national development plans in order to promote a healthy building market by gradually developing the entire national economy while taking into account interrelationships with other sectors of the economy. In terms of private participation and financing, infrastructure is one of the world’s fastest growing sectors. The lack of debt continues to be a major stumbling block for many private infrastructure projects. Due to a worldwide financial crisis, many developing countries have had reduced access to capital markets. Due to a global drop in lending, increasing investor uncertainty, and a lower willingness to assume risk, many developing countries have had less access to capital markets. "What has to be done to increase FDI to developing countries?" is the question. There is plenty of room for positive growth and access to new money in developing countries. However, in order to realise such benefits, these countries must first create the necessary legal, financial, and technological infrastructure. International capital market integration will continue to expand access to private foreign finance for emerging countries. In order to access the international financial markets and secure the necessary finance for their PPI (Private Participation in Infrastructure) projects, policymakers must adjust their policies to fit investors’ interests. Infrastructure private participation is here to stay, and as more developing countries open their doors to private investors, the policy debate has shifted from "whether to" to "how to." The goal of this thesis is to come up with a strategy that developing countries can use to finance construction investment, particularly in infrastructure, by improving and streamlining access to domestic and international capital markets.